Infrared spectral analysis of plasmonic polarons in doped P3HT films - Rohnacher, Valentina; Tzschoppe, Michael; Sivanesan, Vipilan; Pucci, Annemarie (Physica status solidi. B, Basic solid state physics, 2021)
The strong midinfrared polaronic signal in p-doped polymers such as P3HT is analyzed in terms of a plasmonic absorption cross section. Quantitative conclusion on the hole mobility along chains of coherently connected thiophene units is derived in that way. This intrachain mobility is more than two orders of magnitude higher than average mobilities of doped polymers which is limited by the much less efficient interchain transport processes.
Gesehen am 27.03.2023